Mixture of inorganic solids

JP2025501244AActive Publication Date: 2025-01-17ARKEMA FRANCE SA
View PDF 20 Cites 0 Cited by

Patent Information

Application Number
JP2024539554
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-31
Filing Date
2022-12-12
Publication Date
2025-01-17
Estimated Expiration
2042-12-12

AI Technical Summary

Benefits of technology

【0019】 これは、本発明者らが、容器に充填された一組の粒子を高密度化、すなわちより高密度化することができ、特に、触媒プロセス又は吸着若しくは分離プロセスにおいて、好ましくは吸着分離プロセスにおいて一般に使用されるゼオライト凝集体の床(モレキュラーシーブとも呼ばれる)、固定床及び模擬移動床の両方だけでなく、触媒の粒子の床も高密度化することができる単純で経済的かつ効果的な手段を発見したからである。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025501244000001
    Figure 2025501244000001
  • Figure 2025501244000002
    Figure 2025501244000002
  • Figure 2025501244000003
    Figure 2025501244000003
Patent Text Reader

Abstract

The present invention relates to a mixture comprising at least a first group P1 of inorganic solids with a volume mean diameter VAD1 and a second group P2 of inorganic solids with a volume mean diameter VAD2, the VAD2 / VAD1 ratio being between 0.10 and 0.60 (boundary values ​​included). The invention also relates to the use of said mixture for catalytic reactions or separation or drying operations on gases and / or liquids.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of zeolite aggregates, and more specifically to beds of zeolite aggregates. [Background technology]

[0002] Today, industry widely uses zeolite aggregates in various fields, for example in gas or liquid separation, purification, drying, catalysis. In these various techniques of separation, purification, drying or other catalysis, liquids or gases are brought into contact with said zeolite aggregates for more or less long periods of time. The techniques widely used today make use of beds of aggregates through which the liquid or gas to be treated passes. These beds of aggregates are most often packed in columns, tubes, cartridges or other comparable containers, allowing the entry of the liquid or gas to be treated and the discharge of said liquid or gas after treatment. Moreover, these containers must be able to withstand more or less considerable pressures specific to the processes used.

[0003] Zeolite aggregates are typically particles having sizes that may range from tens of nanometers to tens of millimeters, and indeed even hundreds of millimeters. However, there are recurring problems with the methods and techniques used to fill vessels, i.e., to densify beds of zeolite aggregates, since it is desired to densify the beds of zeolite aggregates to make available the greatest amount of zeolite aggregates possible in the smallest possible space, with the goal of further improving the efficiency and profitability of industrial facilities.

[0004] To date, various processes or methods aimed at the densification of such beds of zeolite aggregates are already known. The common objective targeted is a better occupation of the volume containing the zeolite aggregates in order to maximize the amount of solids, which should be done as homogeneously and uniformly as possible in a reproducible manner, without sacrificing the packing time. In the majority of cases, these are "mechanical" devices and processes well known to those skilled in the art, such as, for example: - a homogeneous distribution of particles in the chamber due to the rain effect over the entire cross section of this chamber, as in document US 2 655 273, - Fixtures of equipment in which particles are dispersed by means of compressed air, as per document FR2288560A1, - rotating devices for the direct dispersion of particles, as described in particular in documents FR 2 087 890, FR 2 153 380 and FR 2 319 427 A1, - a mobile device comprising a shaft driven in rotation by motor means, such as those in documents EP 007854 A1 and EP 116246 A1, and several stages of flexible deflection elements, such as strips.

[0005] More specifically, among these devices known to those skilled in the art, sock filling consists of manually pouring the solid particles using a flexible conduit called a "sleeve" or "sock". Thus, patent application US2020353434A1 describes a new sock system for sock filling, which can take a spiral shape to limit the movement of the solids and thus prevent their deterioration.

[0006] Further "high density" packing techniques are described in the following literature: - No. FR 2721900, which describes in detail the Catapac® process and makes it possible to achieve a packing density at least 10% greater than the sock-type packing described above; - EP 0 769 462 A1 and WO 2006 013 240 A1, which teach the dense packing process, currently known under the name Densicat®, combining a device and a process for packing divided solids into containers, in particular for packing solids, which may be provided in the form of beads, particles, cylinders, etc., into fixed beds of chemical or electrochemical, petroleum or petrochemical type.

[0007] More recently, increasingly sophisticated devices allow the loading and unloading of zeolite aggregates, as shown for example by documents CN111634681A and US2021146326A1, which describe loading and unloading devices for adsorbents with very specific feeding systems.

[0008] In connection with or as an alternative to these mechanical filling devices or processes, there are also methods that use lubricants in solid form. These methods are used in particular in the pharmaceutical, cosmetic, food processing and petrochemical industries with the aim of improving the flowability of mixtures of zeolite crystals or zeolite aggregates. This is because flowability is an important property for many processes, for example when these crystals or aggregates have to pass through a feed hopper. Therefore, in order to ensure a flow that is as fluid as possible and results in tablets of uniform weight, most pharmaceutical processes today incorporate a preliminary step of mixing with a lubricant. The latter distributes on the surface of said crystals or aggregates, thus improving their flowability.

[0009] To illustrate this technology, reference can be made for example to application WO2019120938A1, which describes a process of filling a chamber with solid particles that have previously been subjected to a pretreatment, which consists in mixing said solid particles, before filling them into the chamber, with at least one solid lubricant selected from saturated fatty acids having 14 or more carbon atoms, their metal salts, esters, fatty alcohols having 14 or more carbon atoms, linear n-alkanes having 16 or more carbon atoms in solid form, fumaric acid, talc and sodium stearyl fumarate. The lubricant is introduced at ambient temperature and in a content of between 0.01% and 1% by weight relative to the total weight of the mixture of solid particles and lubricant.

[0010] Patent US7927555B2 describes, among other things, a process for filling particles of a catalyst with a specific liquid, such as water or an organic compound having a boiling point above 100° C. under atmospheric pressure.

[0011] However, these techniques with solid or liquid lubricants present the drawback of requiring a step to remove said lubricant after loading of the particles, since the lubricant may reduce the performance or efficiency of the adsorbent or catalyst. Furthermore, this technique may raise concerns regarding the presence of residual organic compounds, which may result in coking, deposits, clogging, etc.

[0012] Other methods of particle packing are presented, inter alia, in document WO2015107322, where catalyst particles are packed radially in a column on the one hand and smaller sized particles are packed axially in this column on the other hand. Patent EP0891802B1 provides a particle packer intended to pack particles into a vessel to form a bed of particles having an outer concentric layer and an inner concentric layer, the particles of the inner and outer layers differing both in size and composition.

[0013] These techniques, which may be described as "mechanical", present the drawback of requiring relatively complex devices to pack some groups of particles in one specific configuration and other groups of particles in another specific configuration. [Prior art documents] [Patent documents]

[0014] [Patent Document 1] U.S. Patent No. 2,655,273 [Patent Document 2] French Patent Application Publication No. 2288560 [Patent Document 3] French Patent Application Publication No. 2087890 [Patent Document 4] French Patent Application Publication No. 2153380 [Patent Document 5] French Patent Application Publication No. 2319427 [Patent Document 6] European Patent Application Publication No. 007854 [Patent Document 7] European Patent Application Publication No. 116246 [Patent Document 8] US Patent Application Publication No. 2020 / 353434 [Patent Document 9] French Patent No. 2721900 [Patent Document 10] European Patent Application Publication No. 0769462 [Patent Document 11] International Publication No. 2006 / 013240 [Patent Document 12] China Patent Application Publication No. 111634681 [Patent Document 13] US Patent Application Publication No. 2021 / 146326 [Patent Document 14] International Publication No. 2019 / 120938 [Patent Document 15] U.S. Patent No. 7,927,555 [Patent Document 16] International Publication No. 2015 / 107322 [Patent Document 17] European Patent No. 0891802 Summary of the Invention [Problem to be solved by the invention]

[0015] The present invention aims to overcome the above mentioned problems encountered with known filling methods of the prior art.

[0016] A first objective is therefore to provide a means allowing dense and optimized packing of containers of solid particles, e.g. columns intended to receive solid particles such as zeolite aggregates or catalyst particles, etc. Another objective is to prevent packing of the front slope, or at least to prevent packing of the front slope of more than 10%.

[0017] Another objective is to increase the amount of active phase in a bed of zeolite aggregates or catalyst for a given volume in order to further improve the efficiency of the zeolite aggregates or catalyst, respectively. [Means for solving the problem]

[0018] The above objects are achieved in whole or at least in part by the present invention, as described below. Further objects will become apparent in the description of the invention set forth below.

[0019] This is because the inventors have discovered a simple, economical and effective means by which a set of particles packed in a vessel can be densified, i.e. made more dense, and in particular beds of catalyst particles as well as beds of zeolite aggregates (also called molecular sieves), both fixed beds and simulated moving beds, commonly used in catalytic processes or adsorption or separation processes, preferably in adsorption separation processes.

[0020] Thus, according to a first aspect, the invention relates to a mixture comprising at least a first group P1 of inorganic solids of volume mean diameter VAD1 and a second group P2 of inorganic solids of volume mean diameter VAD2, the VAD2 / VAD1 ratio being between 0.10 and 0.60 (limits included), preferably between 0.15 and 0.55 (limits included), advantageously between 0.20 and 0.50 (limits included) and more particularly between 0.25 and 0.50 (limits included). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] In one embodiment of the invention, the inorganic solids of group P1 exhibit a volume average diameter VAD1 between 0.4 mm and 5 mm, preferably between 0.4 mm and 2.5 mm, more preferably between 0.4 mm and 1 mm and very particularly preferably between 0.4 mm and 0.8 mm (limit values ​​included).

[0022] The mixtures according to the invention generally preferably comprise a quantity of group P2 of inorganic solids such that it does not result in a substantial variation of the volume mean diameter (VADm) of the mixture compared to VAD1. More specifically, the mixtures according to the invention exhibit a VADm / VAD1 ratio higher than 0.85, preferably higher than 0.88 and more preferably higher than 0.90.

[0023] In a preferred embodiment of the invention, the amount of inorganic solids of the second group P2 corresponds to up to 25% by weight, preferably up to 15% by weight, for example 0.5% to 25% by weight, better still 1% to 15% by weight (limits included), relative to the combined P1+P2 inorganic solids.

[0024] In general, with respect to the above-mentioned ratio VAD2 / VAD1, the inorganic solids of group P2 exhibit a volume-average diameter VAD2 of less than 2 mm, preferably less than 1 mm, more preferably less than 0.5 mm, more particularly less than 0.4 mm, typically less than 0.3 mm. According to a preferred embodiment, the volume-average diameter VAD2 is greater than 0.05 mm, more preferably greater than 0.1 mm. Thus, according to yet another preferred embodiment, the volume-average diameter VAD2 is between 0.05 mm and 2 mm, preferably between 0.05 mm and 1 mm, more preferably between 0.05 mm and 0.5 mm, more particularly between 0.1 mm and 0.4 mm, typically between 0.1 mm and 0.3 mm (boundary values ​​included).

[0025] In a particularly preferred embodiment of the invention, the latter relates to a mixture of inorganic solids consisting of at least two groups P1 and P2, just as defined.

[0026] The inorganic solids of groups P1 and P2 can be of any nature. However, the invention is very particularly suitable for inorganic solids selected from adsorbents in general, such as zeolites, aluminas, silica gels and catalysts, more specifically zeolite aggregates, also called molecular sieves, and solid catalysts, whether in the form of powders, beads, crushed materials, extrudates, yarns, mouldings or any other form known to the skilled artisan, preferably in the form of beads. Preference is given to zeolite aggregates, also called molecular sieves, among which are aggregates of zeolite crystals with at least one binder, organic or inorganic, preferably inorganic, such as clay or a mixture of clays.

[0027] In a preferred embodiment of the mixture of the invention, the inorganic solids of groups P1 and P2 are of the same chemical nature or at least sufficiently close, i.e. the two groups contribute to the same desired goal during use of the mixture. According to a completely preferred embodiment, the inorganic solids of groups P1 and P2 are of the same chemical nature.

[0028] Without wishing to be bound by theory, it can be assumed that the inorganic solids of groups P1 and P2 act as "lubricants" relative to each other, which results in a reduction in the free space between the particles of the inorganic solids compared to that observed with a single group of inorganic solid P1 or a single group of inorganic solid P2, and therefore in a densification, in other words an increase in the volume, of the mixture present in the container.

[0029] The present invention is particularly suitable for zeolite aggregates and catalytic solid particles.

[0030] According to yet another preferred embodiment of the invention, the inorganic solids of group P2 exhibit an average circularity higher than 60%, more preferably higher than 80% and most preferably higher than 90%.

[0031] The average circularity, expressed as a percentage, is calculated from the moments of the distribution of circles inscribed in the particle and tangent to the points of the particle's contour, according to complex filtering, as shown in document WO2008152319. It represents the variation of the particle's radius of curvature and reflects the maturity of the solid in the wear process. Mild bumps are more important than very pronounced bumps. The closer to perfect sphericity, the closer the circularity is to 100%.

[0032] In one embodiment, the mixture according to the invention advantageously exhibits a bed crushing strength, typically between a few hundred kPa and a few tens of MPa, generally between 0.3 MPa and 3.2 MPa, preferably between 0.3 MPa and 2.5 MPa. The method of measuring the bed crushing strength and other analytical methods are described later in the specification.

[0033] The mixture according to the invention is particularly well suited for adsorbent zeolite aggregates, whether they be molecular sieves or catalyst particles. The mixture according to the invention is very particularly well suited for solid particles of zeolite aggregates.

[0034] According to a preferred embodiment, the mixture of the invention comprises or consists of an inorganic solid which is an aggregate of zeolite crystals, well known to those skilled in the art and already widely described in the scientific and patent literature.

[0035] As non-limiting examples, the zeolite aggregates contained in the mixtures of the invention are aggregates of zeolite crystals, the zeolites being selected from LTA type zeolites, preferably 3A, 4A and 5A zeolites, FAU type zeolites, preferably X, LSX, MSX or Y type zeolites, MFI type zeolites, preferably ZSM-5 type zeolites and silicalites, zeolite P, SOD type zeolites (such as sodalite), MOR type zeolites, CHA type zeolites (such as chabazite), HEU type zeolites (such as clinoptilolite) and homologues with hierarchical porosity, as well as mixtures comprising two or more of these in any proportion.

[0036] With regard to the requirements of the present invention, preferred are aggregates of zeolites selected from LTA type zeolites, preferably 3A, 4A and 5A zeolites, FAU type zeolites, preferably X, LSX, MSX or Y type zeolites, zeolite P, SOD type zeolites (such as sodalite), MOR type zeolites, CHA type zeolites (such as chabazite), HEU type zeolites (such as clinoptilolite) and homologues with hierarchical porosity, and mixtures comprising two or more of these in any proportion.

[0037] The above zeolites may be natural, artificial or synthetic, and if reduced, natural, modified or synthetic. Zeolites generally contain one or more types of cations to ensure electronic neutrality. The cations present in zeolites, either naturally or after one or more cation exchanges, are well known to those skilled in the art. Non-limiting examples of such cations include cations of hydrogen, cations of alkali metals, cations of alkaline earth metals, cations of metals from groups VIII, IB and IIB, and mixtures of two or more of these, and general examples of cations include cations of lithium, potassium, sodium, barium, calcium, silver, copper, zinc, and mixtures of two or more of these in any proportion.

[0038] Very particularly preferred mixtures according to the invention comprise, as non-limiting examples, at least a first group P1 of zeolite aggregates and at least a second group P2 of zeolite aggregates, which are identical or different and are selected from aggregates of zeolites LTA (such as 3A, 4A or 5A), X, LSX, MSX and Y.

[0039] Specific examples of mixtures according to the invention include mixtures of zeolite LTA agglomerates, e.g. mixtures of zeolite 3A and zeolite 4A, or of zeolite 4A agglomerates and zeolite 5A agglomerates, mixtures of zeolite LSX agglomerates and zeolite X agglomerates, mixtures of zeolite MSX agglomerates and zeolite X agglomerates, mixtures of zeolite LSX agglomerates and zeolite MSX agglomerates, mixtures of zeolite X agglomerates and zeolite Y agglomerates, mixtures of zeolite 4A agglomerates and zeolite X agglomerates, to mention only a few.

[0040] According to a preferred embodiment of the present invention, the inorganic solids of groups P1 and P2 are of the same nature, i.e. form a mixture selected from the group comprising, as non-limiting examples, mixtures of zeolite aggregates based on zeolite LTA (e.g. mixtures of zeolite aggregates based on zeolite 3A, mixtures of zeolite aggregates based on zeolite 4A), mixtures of zeolite aggregates based on zeolite LSX, mixtures of zeolite aggregates based on zeolite MSX, mixtures of zeolite aggregates based on zeolite X, mixtures of zeolite aggregates based on zeolite Y, mixtures of zeolite aggregates based on zeolite MFI, mixtures of zeolite aggregates based on zeolite EMT, etc.

[0041] According to another embodiment of the invention, the inorganic solids of groups P1 and P2 are of different nature, i.e. they form a mixture selected from the group comprising, by way of non-limiting example, a mixture of zeolite aggregates based on zeolite X and agglomerates based on zeolite LSX, a mixture of zeolite aggregates based on zeolite X and agglomerates based on zeolite MSX, a mixture of zeolite aggregates based on zeolite MSX and agglomerates based on zeolite LSX, a mixture of zeolite aggregates based on zeolite X and agglomerates based on zeolite Y, a mixture of zeolite aggregates based on zeolite X and agglomerates based on zeolite 4A, a mixture of zeolite aggregates based on zeolite 4A and agglomerates based on zeolite 5A, to mention only a few.

[0042] The mixtures according to the invention can be prepared by any means known to those skilled in the art, for example by simple mechanical mixing of the inorganic solids of groups P1 and P2 using a conventional stirrer, for example a blade stirrer, during the direct filling of said mixture into the desired container, or via a feed hopper having a common filling conduit.

[0043] The mixture according to the invention makes it possible to fully or partially address the shortcomings encountered in the prior art and, very particularly, to improve the packing density of containers with inorganic solid particles, in particular as defined above.The mixture according to the invention therefore makes it possible to densify beds of solid inorganic particles, while avoiding resorting to organic lubricants that may be difficult to remove and / or may remain at least partially in said mixture.As mentioned above, in the mixture according to the invention, the lubricating effect is observed by a specific ratio of the volume mean diameters of groups P1 and P2.

[0044] According to a preferred embodiment, the mixture according to the invention allows an increase in the packing density of the groups of more than 2%, preferably more than 5%, more preferably more than 7% and advantageously more than 10%, relative to the packing density of group P1.

[0045] Another advantage of the mixtures of the invention lies in the fact that a premixing step can be eliminated by simultaneously filling the container with the inorganic solids of groups P1 and P2. Due to the observed lubricating effect, the inorganic solid particles fill the container in a dense manner without having to resort to other alternating filling techniques, radial / axial or otherwise, and without having to resort to complex equipment aimed at filling the container homogeneously, as is common in the prior art.

[0046] Thus, the filling of the mixture according to the invention into a container can be carried out starting from a mixture of inorganic solid particles of groups P1 and P2, either directly or by simultaneous filling as indicated above. Optionally, if desired, in order to further improve the homogeneous distribution of the mixture according to the invention in the desired container, it is possible to use one or more auxiliary means to aid the dense filling of the mixture according to the invention, which are well known to the skilled person and can be selected, as non-limiting examples, from vibration means, flexible sleeves, means with blades, etc. However, although such means are generally not preferred, the mixture according to the invention shows quite unexpected flowability, which results in an easier filling, especially in beds, not yet observed with the techniques described in the prior art.

[0047] Furthermore, it was observed that the mixtures according to the invention with groups P1 and P2, whose VAD2 / VAD1 ratio is as claimed, have a positive effect on the mass transfer in the application (reduction of the mass transfer zone compared to that observed for group P1). In particular, in some cases, a reduction in the porosity of the bed could be observed without a significant increase in the pressure drop.

[0048] The mixtures according to the invention are particularly suitable for filling containers in an optimal way, i.e. with an optimized amount of particles of inorganic solids per unit volume. This effect of optimizing the amount per unit volume, i.e. "densification", is due in particular to the very good flowability of the mixtures according to the invention. This property can be observed for all sizes of inorganic solids groups, as shown above.

[0049] Moreover, it has been observed that the improved flowability achieved by the particular VAD1 / VAD2 ratios mentioned above prevents the degradation often observed during filling of the mixtures according to the invention due to degradation, attrition, crushing etc., particularly when passing through the filling hopper.

[0050] The mixtures according to the invention also present the advantage of being suitable for all sizes of containers, whether these are columns, tubes, reactors, etc. The above-mentioned good flow properties of the mixtures according to the invention ensure very good homogeneity of the densification and packing during packing, making it possible to substantially optimize the flow hydrodynamics in the target application.

[0051] The mixtures according to the invention therefore find use in numerous fields of application, for example but not limited to, separation of gases and / or liquids, drying operations on gases and / or liquids, separation of organic molecules such as, for example, hydrocarbons in the gas and / or liquid phase, catalytic reactions in the gas and / or liquid phase, whether in static or dynamic mode.

[0052] The following examples illustrate the invention without limiting its scope, which is defined by the appended claims. The physical properties of the aggregates according to the invention were evaluated by methods known to those skilled in the art, the main ones being listed below.

[0053] <Measurement method> <Loss on ignition (LOI)> The loss on ignition is measured in an oxidizing atmosphere by firing the sample in air at a temperature of 950° C.±25° C., as described in standard NF EN 196-2 (April 2006). The standard deviation of the measurements is less than 0.1%.

[0054] <density> According to the size of the agglomerated material to be tested, the bulk density of the zeolite agglomerated material according to the invention is measured as described in standard DIN 8948 / 7.6 or standard ASTM D4164.

[0055] To determine the filling density, a given amount of the agglomerated bead mixture is introduced into a graduated measuring cylinder of 250 ml. The test specimen is placed in a tamping system (JEL STAV 2003 Stampf type impact system) and subjected to an impact of 10 minutes, i.e. 2400 J. The fact that a constant volume has been obtained is verified by adding an additional 2 minutes of tamping. The filling density (or packed density) is then calculated by measuring the weight and the occupied volume of the mixture in the test specimen. Before carrying out the measurement, the agglomerates are left to regain moisture in order to ensure that there are no weight variations during the density measurement.

[0056] Loss on ignition (LOI) measurements are made so that density measurements can be converted back to anhydrous values.

[0057] <Volume average particle diameter> The volume mean diameter of inorganic solid particles is determined by analyzing the particle size distribution of a sample of the adsorbent material using a CamSizer® device from Microtrac by imaging it according to standard ISO 13322-2:2006, using a conveyor belt that allows the sample to pass in front of the camera lens.

[0058] The volume mean diameter is then calculated from the particle size distribution applying standard ISO 9276-2:2001, with an accuracy of the order of 0.01 mm for the range of volume mean diameters of solid particles that can be used in the context of the present invention.

[0059] <Measurement of roundness> For each sample tested, an acquisition is made on 10,000 particles using an Alpaga 500 Nano device, and the elongation and circularity parameters are calculated for each particle. The mathematical tools used for their calculation are developed in the medical theory of E. Pirard (1993, University of Liege, p. 253) entitled "Morphometrie euclidienne des figure planes. Applications a lanalyse des materiaux granulaires" (Euclidean morphometry of flat figures. Applications in the analysis of granular materials). The document entitled "The descriptive and quantitative representation of particle shape and morphology" is available under the reference ISO / DIS 9276-6.

[0060] The average circularity is expressed as a percentage and is calculated from the moments of the distribution of circles inscribed in the particle and tangent to the points of the particle's contour, following complex filtering as already mentioned above. It represents the variation of the particle's radius of curvature and reflects the particle's maturity in the wear process. Mild bumps are more important than very pronounced bumps. The closer the particle's shape is to a perfect sphere, the closer the circularity is to 100%.

[0061] <Mechanical strength> The method chosen to characterize the mechanical strength of the mixture of inorganic solids of the invention is standard ASTM D7084-04, which allows to determine the crush resistance of a solid bed. 3 A sample of the aggregate is subjected to an increasing force via a piston against the stationary phase.

[0062] The fines obtained in the various hydrostatic phases are separated by sieving and weighed. The sieves used are suitable for agglomerates smaller than 1000 μm in size. For mixtures with a volume mean diameter between 500 μm and 1000 μm, between 180 μm and 500 μm and between 50 μm and 180 μm, respectively, sieves of 200 μm, 80 μm and 40 μm are used.

[0063] On a graph representing the accumulated weight of fines obtained as a function of the force applied to a bed of a mixture of solid particles, the bed crushing strength (BCS) was determined by interpolation of the applied load at 0.5% by weight of accumulated fines and calculation of the corresponding pressure expressed in MPa, the interpolated force being related to the surface area of ​​the inner section of the cylinder. EXAMPLES

[0064] [Example 1 (according to the present invention)] Two adsorbents were prepared from X-type faujasite zeolite crystals, with the number-average size of the crystals being 0.6 μm.

[0065] <Preparation of Adsorbent 1 (Group P1)> A homogeneous mixture is prepared, agglomerating 800 g of zeolite crystals with 160 g of kaolin (expressed as calcined equivalent) and 60 g of colloidal silica sold under the trade name Klebosol® 30N50 (containing 30% by weight of SiO2 and 0.5% by weight of Na2O) in an Eirich nodulating mixer. The agitator is started and water is gradually introduced until the moisture content of the mixture reaches about 36%. The agitator speed is adjusted to prepare beads with an average size of about 0.7 mm. Agglomerates larger than 1 mm in size and fines smaller than 0.315 mm in size are removed by sieving. The beads thus obtained are dried and then calcined under a nitrogen flow at 550 ° C for 2 hours (calcination of the clay). The volume average diameter VAD1 of the beads obtained (group P1) is 0.662 mm and the packing density (back to anhydrous) is 0.613.

[0066] <Preparation of Adsorbent 2 (Group P2)> A second adsorbent is prepared according to the same protocol, but with an increased stirring speed in order to obtain agglomerates with an average size close to 0.150 mm. The agglomerates are subsequently ground in a bowl granulator to form uniform beads. A selection by sieving is carried out to obtain beads with a size between 0.08 mm and 0.180 mm. The beads are dried and then calcined at 550 ° C for 2 hours under a nitrogen flow (calcination of the clay). The volume average diameter VAD2 of the resulting beads (group P2) is 0.137 mm and the packing density (back to anhydrous) is 0.563.

[0067] <Characteristics of Group P1 + Group P2 Mixture> A mixture of groups P1 and P2 in a proportion of 90% by weight of P1 and 10% by weight of P2 is then prepared in a Turbula helical mixer, the VAD2 / VAD1 ratio being equal to 0.21.

[0068] The value of the volume mean diameter (VADm) of the mixture by the above method is very close to the volume mean diameter of Group 1 (VAD1 = 0.662 mm), more specifically, VADm / VAD1 = 0.87.

[0069] The packing density of the mixture was also measured and shows an increase of 10.7% compared to the packing density observed for Group 1.

[0070] This example clearly shows that the mixture according to the invention makes it possible to substantially increase the packing density of group 1 while keeping the volume mean diameter substantially unchanged.

[0071] [Example 2 (according to the present invention)] Adsorbent 3 is prepared following the same protocol used for adsorbent 2, also varying the stirring speed to obtain agglomerates with an average size close to 0.20 mm. The agglomerates are then ground in a bowl granulator to form uniform beads. Selection by sieving is carried out to obtain beads with a size between 0.125 mm and 0.315 mm. The beads are dried and then calcined at 550 °C for 2 h under a nitrogen flow (calcination of clay).

[0072] The volume mean diameter VAD2 of the beads obtained (group P2) and their packing density (reverted to the anhydrous form) are 0.210 mm and 0.574 respectively.

[0073] <Characteristics of Group P1 + Group P2 (Adsorbent 3) Mixture> A mixture of groups P1 (from example 1) and P2 (adsorbent 3 prepared above) is then prepared in a Turbula helical mixer in proportions of 90% by weight of P1 and 10% by weight of P2, the VAD2 / VAD1 ratio being equal to 0.32.

[0074] The value of the volume mean diameter (VADm) of the mixture by the above method is very close to the volume mean diameter of group 1 (VAD1 = 0.662 mm), more specifically, VADm / VAD1 = 0.89.

[0075] The packing density of the mixture was also measured and shows an increase of 9.4% compared to the packing density observed for Group 1.

[0076] This example clearly shows that the mixture according to the invention makes it possible to substantially increase the packing density of group 1 while keeping the volume mean diameter substantially unchanged.

[0077] [Example 3 (according to the present invention)] A new adsorbent, adsorbent 4, is prepared in the same way as adsorbents 2 and 3 above, but also varying the stirring speed to obtain agglomerates with an average size close to 0.30 mm. The agglomerates are passed through a drum granulator and then selected by sieving to obtain beads with a size between 0.18 mm and 0.40 mm. The beads are dried and then calcined at 550 °C for 2 hours under a nitrogen flow (calcination of the clay). The volume average diameter VAD2 of the resulting beads (group P2) and their packing density (back to anhydrous) are 0.318 mm and 0.606, respectively.

[0078] <Characteristics of Group P1 + Group P2 (Adsorbent 4) Mixture> A mixture of groups P1 (from example 1) and P2 (adsorbent 4) is then prepared in a Turbula helical mixer in proportions of 90% by weight of P1 and 20% by weight of P2, the VAD2 / VAD1 ratio being equal to 0.48.

[0079] The value of the volume mean diameter (VADm) of the mixture by the above method is very close to the volume mean diameter of group 1 (VAD1 = 0.662 mm), more specifically, VADm / VAD1 = 0.89.

[0080] The packing density of the mixture was also measured and shows an increase of 7.1% compared to that observed for Group 1.

[0081] This example clearly shows that the mixture according to the invention makes it possible to substantially increase the packing density of group 1 while keeping the volume mean diameter substantially unchanged.

[0082] [Comparative Example 1] Prepare another adsorbent following the same protocol (following the protocol described above for adsorbents 3 and 4) while varying the stirring speed to obtain agglomerates with an average size close to 0.45 mm.

[0083] The agglomerates are then ground in a drum granulator to form uniform beads. Sieving selection is performed to obtain beads with a size between 0.40 mm and 0.50 mm. The beads are dried and then calcined at 550°C for 2 hours under a nitrogen flow (calcination of the clay).

[0084] The volume mean diameter VAD2 of the beads obtained (group P2) and their packing density (reverted to the anhydrous form) are 0.441 mm and 0.607 respectively.

[0085] <Characteristics of Group P1 + Group P2 (Comparative Adsorbent 1) Mixture> A mixture of groups P1 and P2 (compound 1) is then prepared in a Turbula helical mixer in proportions of 90% by weight of P1 and 10% by weight of P2, the VAD2 / VAD1 ratio being equal to 0.67.

[0086] The volume average diameter (VADm) value of the mixture by the above method is substantially the same as the volume average diameter value of Group 1 (VAD1 = 0.662 mm), more specifically, VADm / VAD1 = 0.97.

[0087] The packing density of the mixture was also measured and it is noted that compared to the packing density observed for Group 1, there is no increase in density and in fact there is even a loss in density of about 0.4%.

[0088] The values ​​obtained in Examples 1, 2 and 3 and Comparative Example 1 are summarized in Table 1 below.

[0089] [Table 1]

Claims

1. A mixture comprising at least a first group P1 of inorganic solids with a volume mean diameter VAD1 and a second group P2 of inorganic solids with a volume mean diameter VAD2, the ratio VAD2 / VAD1 being between 0.10 and 0.60 (limits included), preferably between 0.15 and 0.55 (limits included), advantageously between 0.20 and 0.50 (limits included), more particularly between 0.25 and 0.50 (limits included).

2. 2. The mixture according to claim 1, wherein the inorganic solids of group P1 exhibit a volume average diameter VAD1 between 0.4 mm and 5 mm, preferably between 0.4 mm and 2.5 mm, more preferably between 0.4 mm and 1 mm, very particularly preferably between 0.4 mm and 0.8 mm (limits included).

3. 3. The mixture according to claim 1 or claim 2, having a VADm / VAD1 ratio higher than 0.85, preferably higher than 0.88, more preferably higher than 0.90, where VADm represents the volume mean diameter of the mixture.

4. 4. The mixture according to any one of claims 1 to 3, wherein the amount of inorganic solids of the second group P2 represents up to 25% by weight, preferably up to 15% by weight, for example between 0.5% and 25% by weight, better still between 1% and 15% by weight, limits included, relative to the combined P1+P2 inorganic solids.

5. 5. The mixture according to any one of claims 1 to 4, wherein the inorganic solids of group P2 have a volume-average diameter of less than 2 mm, preferably less than 1 mm, more preferably less than 0.5 mm, more particularly less than 0.4 mm, typically less than 0.3 mm.

6. 6. The mixture according to claim 1, wherein the inorganic solids of group P2 have a volume-average diameter greater than 0.05 mm, more preferably greater than 0.1 mm.

7. 7. The mixture according to claim 1, wherein the inorganic solids, whether in the form of powders, crushed materials, extrudates, yarns, moulded bodies or in any other form, are chosen from adsorbents and catalysts, and more particularly from zeolite aggregates, also called molecular sieves, and solid catalysts.

8. 8. The mixture according to any one of claims 1 to 7, wherein the inorganic solid is an aggregate of zeolite crystals, the zeolite being selected from LTA type zeolites, preferably 3A, 4A and 5A zeolites, FAU type zeolites, preferably X, LSX, MSX or Y type zeolites, MFI type zeolites, preferably ZSM-5 type zeolites and silicalites, zeolite P, SOD type zeolites, MOR type zeolites, CHA type zeolites, HEU type zeolites and homologues with hierarchical porosity, and mixtures of two or more of these in any proportion.

9. 9. The mixture according to any one of claims 1 to 8, selected from a mixture of at least a first group P1 of zeolite aggregates and a mixture of at least a second group P2 of zeolite aggregates, said zeolite aggregates being identical or different and selected from aggregates of zeolites LTA (such as 3A, 4A or 5A), X, LSX, MSX and Y.

10. Use of the mixtures according to any one of claims 1 to 9 for the separation of gases and / or liquids, for drying operations on gases and / or liquids, for the separation of organic molecules in the gas and / or liquid phase, for catalytic reactions in the gas and / or liquid phase and others, in static or dynamic mode.

Citation Information

Patent Citations

  • Preparation method of high-performance TC-5A molecular sieve adsorbent

    CN109126692A

  • Refrigerant desiccant and dryer

    JP2018021706A

  • Agglomerates of adsorber particles and methods for producing such adsorber particles

    US20120305467A1

  • Adsorption loading and unloading device

    CN111634681A

  • Device for the distribution of bulk material in an enclosure

    EP0007854A1